School food environments in the Philippines - Umali, D.J.; Itliong, K.; Anunciado, M.S.; Monville-Oro, Emilita; Gonsalves, Julian Francis; Hunter, D.; Borelli, T.; Mendonce, S. (2023)
School food environments (SFE)- which include school cafeterias, fast-food restaurants, supermarkets, and other forms of food outlets and food vendors found in the vicinity of the school- offer a unique opportunity to address malnutrition among school children. SFE interventions can promote fruit and vegetables consumption, as well as set children on a life-long path of healthy and sustainable eating behaviors.